Treatment of shale gas fracturing wastewater using microbial fuel cells: Mixture of aging landfill leachate and traditional aerobic sludge as catholyte. (1st October 2020) - Feng, Qi; Xu, Longjun; Liu, Chenglun; Wang, Hailong; Jiang, Zao; Xie, Zhouhua; Liu, Yanling; Yang, Zhengxin; Qin, Yongjun
Abstract: The electrochemically active bacteria of catholytes have important effects on the redox and electricity production of microbial fuel cells (MFCs). Landfill leachates are typically heavily contaminated wastewaters containing large quantities of carbon, inorganic nutrients and electrogenesis bacteria. To realize the treatment of wastewater with other wastes, the effects of different volume ratios of aging landfill leachates and traditional aerobic sludge as catholyte on the treatment of shale gas fracturing wastewater (SGFW) by two-chamber microbial fuel cell (MFC) was reported. The removal efficiency and chemical oxygen demand (COD) of the anolyte and catholyte were 61.9 ± 2.4% and 60.3 ± 0.8%, respectively, with a maximum power density of 14.04 W/m 3 in a 25% V/V aging landfill leachate MFC. These values were significantly higher than those of other MFCs, which can be attributed to lower internal cathode resistance, higher electrocatalytic oxidation, reduction performance, and good bacterial biofilm morphology. The microbial community structure showed that aging landfill leachate doping can contribute to the selective enrichment of sustainable power generation and nitrifying bacteria on cathode biofilms. Specifically, the total relative abundances of Gammaproteobacteria, Alphaproteobacteria, Actinobacteria, Bacteroidia and Deinococci increased from 74.4% to 92% in the cathode chamber when comparing 25% V/V aging landfill leachate with 100% V/V aerobic sludge. This study provides a new method for the utilization or degradation of high concentration organic wastewater and treatment of SGFW using an MFC. Graphical abstract: Image 1 Highlights: Aaging leachate successfully worked as a novel catholyte with SGFW as the anolyte. The much higher maximum output power density can be obtained (14.04 W/m 3 ). Approximately 62% COD removal efficiency on anode chamber. Aging leachate contributes to enrichment of the electricity generation community.